2016
DOI: 10.3892/ijo.2016.3832
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of microRNA and transcription factor reveals important regulators and regulatory motifs in adult B-cell acute lymphoblastic leukemia

Abstract: B-cell acute lymphoblastic leukemia (B‑ALL) is an aggressive hematological malignancy and a leading cause of cancer-related mortality in children and young adults. The molecular mechanisms involved in the regulation of its gene expression has yet to be fully elucidated. In the present study, we performed large scale expression profiling of microRNA (miRNA) and transcription factor (TF) by Illumina deep‑sequencing and TF array technology, respectively, and identified 291 differentially expressed miRNAs and 201 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 66 publications
1
10
0
1
Order By: Relevance
“…The remaining reads of ≥15 nucleotides were aligned to a known reference miRNA precursor in the miRBase database (release 19.0; www.mirbase.org/) using Novoalign software (version v2.07.11; www.novocraft.com/). Normalization of read counts, calculation of the relative expression levels of each miRNA and identification of differentially expressed miRNAs were performed as previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining reads of ≥15 nucleotides were aligned to a known reference miRNA precursor in the miRBase database (release 19.0; www.mirbase.org/) using Novoalign software (version v2.07.11; www.novocraft.com/). Normalization of read counts, calculation of the relative expression levels of each miRNA and identification of differentially expressed miRNAs were performed as previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Lin et al identified the relationship between miR‐15a‐5p and FMS‐like tyrosine kinase3 (FLT3). In summary, miR‐15a inhibits FLT3 activity, and MYC suppresses miR‐15a and increases FLT3 activity directly.…”
Section: Mirnas Related To Apoptosis and Proliferationmentioning
confidence: 99%
“…In addition, MYC plays a critical role in regulating STAT5B. Finally, this positive feedback leads to the promotion of cell proliferation in ALL …”
Section: Mirnas Related To Apoptosis and Proliferationmentioning
confidence: 99%
“…In recent years, studies on micro-RNA and transcription factors in leukemia patients have become increasingly mature. For example, the transcription factor MYC can inhibit the expression of the shared target gene FLT3 by miR-15a-5p, and FLT3 plays a crucial role in activating the STAT5A pathway and promoting tumor cell proliferation [92,93], but its specific mechanism of influence on the development of tumor remains to be further investigated. Targeted drugs in mounting numbers for LSCs signaling pathways are being developed, but most of them are still in the stage of animal experiments, and more research is needed to determine the safety and efficacy in humans.…”
Section: Lscs-related Signaling Pathwaysmentioning
confidence: 99%